Determinants of Tunisian consumer purchase intention halal certified products: a qualitative study - Loussaief, Aida; Haque, Ahasanul (Research Publishing Academy (RPA), United Kingdom (UK), 2018)
Tunisia created its own halal certification on 6th March 2013 which is displayed only on exported products. In fact, there are no halal certified products in the Tunisian market. Thus, this study aims to identify the factors that may influence the Tunisian consumer’s intention to purchase a halal certified product if they will be available on the local market. As halal certification is a new phenomenon in Tunisia, this study has used a qualitative exploratory method. Twenty one in-depth interviews have been conducted. Four consumers segments have been identified based on age and religiosity level: “Enthusiasts” (28.57%), “Supporters” (33.33%), “Indifferents” (19.04%) and “Oppositionists” (19.04%). The determinants and the intention to purchase a halal certified product differ significantly across groups. Given that this study is the first one investigating the Tunisian consumer intention toward halal certified products, it provides valuable insight for companies who want to start a halal industry in Tunisia.